European Perspectives on the New Comparative Theology - Francis X. Clooney (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
Dear Colleagues, Comparative theology is a field with a lineage as long as the earliest efforts by believers to engage, understand, learn from and critique other religions. In the 1980s and 1990s, scholars revived the field as timely in light of today's religious diversity. They have given it some new characteristics, tried new methods, and argued for fresh implications, and thus in a real sense reinvented the discipline, affording new energy to the study of religions in practice and in the particular, without undue a priori attention to theoretical presuppositions and issues of method. Now younger theologians in different traditions have further interrogated its presumptions and practices and brought it into conversation with post-colonialism, gender studies, ethnographic research, and a (re)turn to theologies of religious pluralism. This thematic issue focuses on the European context to see how this new field has been received, understood, and critiqued among scholars writing in Europe. Helpful recent secondary sources include Francis X Clooney's Comparative Theology (2010), and his edited volume, with contributions from younger scholars, The New Comparative Theology (2010). Prof. Dr. Francis X. Clooney Dr. John Berthrong Guest Editors